Expanding access to rehabilitation using mobile health to address musculoskeletal pain and disability - Shayo, Mathew J.; Shayo, Pendo; Haukila, Kelvin F.; Norman, Katherine; Burke, Colleen; Ngowi, Kennedy; Goode, Adam P.; Allen, Kelli D.; Wonanji, Vivian Timothy; Mmbaga, Blandina T.; Bettger, Janet Prvu (Frontiers in Rehabilitation Sciences, 2023)
Musculoskeletal (MSK) disorders such as low back pain and osteoarthritis are a leading cause of disability and the leading contributor to the need for rehabilitation services globally. This need has surpassed the availability of trained clinicians; even in urban areas where services and providers are thought to be more abundant, access can be challenged by transportation options and financial costs associated with travel, care and lost time from work. However, continuing standard of fully in-person rehabilitation care for MSK-associated pain and disability may no longer be necessary. With increased ownership or access to even a basic mobile phone device, and evidence for remote management by trained clinicians, some individuals with MSK disorders may be able to continue their rehabilitation regimen predominantly from home after initial evaluation in primary care or an outpatient clinic. This manuscript describes application of a framework we used to culturally and contextually adapt an evidence-based approach for leveraging digital health technology using a mobile phone (mHealth) to expand access to rehabilitation services for MSK-associated pain and disability. We then conducted a multi-level analysis of policies related to the adapted approach for rehabilitation service delivery to identify opportunities to support sustainability. Our study was conducted in Tanzania, a lower-middle income country with their first National Rehabilitation Strategic Plan released in 2021. Lessons learned can be applied even to countries with greater infrastructure or fewer barriers. The seven-step adaptation framework used can be applied in other regions to improve the likelihood of local mHealth adoption and implementation. Our practice and policy assessment for Tanzania can be applied in other regions and used collaboratively with government officials in support of building or implementing a national rehabilitation strategic plan. The work described, lessons learned and components of the plan are generalizable globally and can improve access to rehabilitation services using mHealth to address the significant and increasing burden of disability.